A study on factors contribute to neighbourliness at Taman Cempaka, Melaka Tengah, Melaka / Muhamed Syukri Abd Hamid and Ahmad Zaki Yusof - Abd Hamid, Muhamed Syukri; Yusof, Ahmad Zaki (Faculty of Administrative Science and Policy Studies, 2012)
In this research, we are studying about neighbourliness value in modern era that we see increasingly eroded compare with the previous time. Thus, we choose resident in Taman Cempaka to be our respondent to study on the factors that contributes to neighbourliness. According Sheau (2006) Neighbourliness ties produce the level of trust among them are higher than the less-friendly neighborhood. The study was conducted to identify the factors (Family institution, community union and safety community) contributes towards Neighborliness among residents in Taman Cempaka in Melaka. The studies also determine significant relationship between factors and resident involvement in community programmes. The sampling technique that have been using is sample random technique. The location of Taman Cempaka is quite large and consists of 480 units of house and 210 residents as our respondents. According to the findings, it shows that two factors which are family institutions and community union are the most contributes to the neighbourliness in Taman Cempaka.